2020
DOI: 10.1109/access.2020.3024102
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Learning Behavior in an Automated Programming Assessment Environment: A Code Quality Perspective

Abstract: Automated programming assessment systems are useful tools to track the learning progress of students automatically and thereby reduce the workload of educators. They can also be used to gain insights into how students learn, making it easier to formulate strategies aimed at enhancing learning performance. Rather than functional code which is always inspected, code quality remains an essential aspect to which not many educators consider when designing an automated programming assessment system. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Reporting distinct groups of programming learners is common in the learning analytics literature; however, there are significant differences among disciplines and cluster characteristics pertaining to the context [12,20,31,35,56]. By clustering students' learning tactics, [12] found three distinct groups of learners (highly selective, strategic, intensive), with very similar profiles and performance to those found in this work.…”
Section: Identification Of Types Of Learners According To Their Learning Strategiessupporting
confidence: 57%
See 4 more Smart Citations
“…Reporting distinct groups of programming learners is common in the learning analytics literature; however, there are significant differences among disciplines and cluster characteristics pertaining to the context [12,20,31,35,56]. By clustering students' learning tactics, [12] found three distinct groups of learners (highly selective, strategic, intensive), with very similar profiles and performance to those found in this work.…”
Section: Identification Of Types Of Learners According To Their Learning Strategiessupporting
confidence: 57%
“…Blikstein [18] used the data captured from a programming environment to analyze the changes in the number of code compilations over time, identify moments of greater difficulty in the programming process, and trace an approximation of each prototypical coding profile and style. In the work by Chen et al [20], cluster analysis confirmed that learning motivation (denoted by early and on-time submissions) was strongly associated with final grades, and not the number of submissions made by students. Furthermore, Watson et al [34] developed a unique approach for predicting performance based upon how a student responds to different types of errors compared to their peers.…”
Section: Learning Analytics In Programming Educationmentioning
confidence: 95%
See 3 more Smart Citations